2015
DOI: 10.1002/chem.201503643
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(III)‐Catalyzed Dehydrative [4+2] Annulation of Oxime with Alkyne by CH and NOH Activation

Abstract: Efficient, scalable cobalt-catalyzed redox-neutral [4+2] annulation of readily available oximes and alkyne is reported. The developed synthetic methodology is widely applicable and tolerates various functional groups including heterocycles. A stable Cp*Co(III) neutral complex is employed as the catalyst for this redox-neutral [4+2] annulation reaction, which progresses smoothly by way of a reversible cyclometallation without any external oxidizing agent, and produces only water as the side product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(42 citation statements)
references
References 106 publications
2
40
0
Order By: Relevance
“…In accordance with the above-mentioned precedents, [8,11] a poor outcomew as obtained in the initial experiment using Co(OAc) 2 (20 mol %) in conjunction with Mn(OAc) 2 (2 equiv) as co-oxidant and NaOAc (4 equiv) as ab ase under oxygen atmosphere,a ffording product 2 in 13 %G Cy ield (entry 1). As olvents creening (entries [6][7][8][9][10][11] revealed that ethanol, 1,4-dioxane and DCE are suitable for this transformation( 80-84% GC yield), whereas hexafluoroisopropanol (HFIP) failed to provide 2 in useful conversion (16 %GCy ield, entry 8). In the absence of NaOAc, the catalytic activity was virtuallys uppressed (5 %G Cy ield, entry 2), suggesting that an extra source of acetate ions is necessary for the reactiont o proceed.…”
Section: Optimization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the above-mentioned precedents, [8,11] a poor outcomew as obtained in the initial experiment using Co(OAc) 2 (20 mol %) in conjunction with Mn(OAc) 2 (2 equiv) as co-oxidant and NaOAc (4 equiv) as ab ase under oxygen atmosphere,a ffording product 2 in 13 %G Cy ield (entry 1). As olvents creening (entries [6][7][8][9][10][11] revealed that ethanol, 1,4-dioxane and DCE are suitable for this transformation( 80-84% GC yield), whereas hexafluoroisopropanol (HFIP) failed to provide 2 in useful conversion (16 %GCy ield, entry 8). In the absence of NaOAc, the catalytic activity was virtuallys uppressed (5 %G Cy ield, entry 2), suggesting that an extra source of acetate ions is necessary for the reactiont o proceed.…”
Section: Optimization Studiesmentioning
confidence: 99%
“…[3] This increasing demandt om ove toward more environmentally benign approaches also makes it highly desirable to replace the stoichiometric oxidants generally required to maintain the catalytic cycle (most often silver or copper salts) with molecularo xygen,i nw hich no wastes are formed except for water. [5,6] Consequently,c atalyst systems combinings imple cobalts alts and O 2 as the sole oxidant are being actively sought. In particular,t he first broadly applicable Co-catalyzed aerobic alkyne annulations have appeared only recently.…”
Section: Introductionmentioning
confidence: 99%
“…[20] TheC p*Co III catalyst exhibited much higher site selectivity for unsymmetrical O-acyl oximes and higher reactivity towards terminal alkynes than the Cp*Rh III catalyst.…”
Section: Angewandte Zuschriftenmentioning
confidence: 96%
“…The transition‐metal catalyzed synthesis of isoquinolines via redox‐neutral strategy is well documented in the literature and in that context, many noble metals have been used . Nonetheless, Co III ‐catalyzed redox‐neutral directed synthesis of isoquinolines was not reported and very recently, this was independently achieved by Kanai/Matsunaga, Ackermann, Sundararaju, and Cheng from the coupling of various oximes with alkynes. A variety of functional groups on oximes and different type of alkynes, including aliphatic alkynes, terminal alkynes were well tolerated, and excellent regioselectivity was observed with internal alkynes under these reaction conditions.…”
Section: Cocp* Catalyzed Annulation Reactionsmentioning
confidence: 99%